'What happened to her eyes?': Self-sacrifice in [REC]. Issue 2 (1st October 2019) - McKeown, Will
This study examines the concept and practice of self-sacrifice in the Spanish horror film [REC] (Balagueró and Plaza, 2007). By resituating the camera in the diegesis of the plot, this film, as is the case with other found footage and cinéma-vérité film, complicates notions of selfhood by fusing personal and cinematic perspectives. Superseding the assumption that the camera stands in for the eyes of the audience, the camera/self model develops from the notion that the camera signifies otherwise unknowable information about its operator that an audience can identify with. The construction of this self-signified point of view will be analysed through the applicationof Lacanian frameworks, starting with the mirror stage and incorporating a reassessment of Baudry's apparatus theory in terms of its possible application to both found-footage film and cinéma-vérité. This analysis will thereby interpret how represented self-sacrifices in [REC] combine to form a signifying chain (Lacan 1966). The analysis holds that the slippage of meaning can be read as a survivalist symptom with which the mostly hand-held, vérité style camera/self can identify. Indeed, this is achieved because the camera/self is simultaneously experiencing and documenting the violence of the self-sacrifice. Analyses of key scenes will employ Lacan's metaphorical/metonymical framework in order to trace the symbolic chain through its underlying drives of the Real. The limits of the film's signification will indicate the impetus of character motivations (Real drives) as they seek to transgress them through the cinematic frame, the imposed quarantine and the geographic boundaries beyond it. This article thus investigates how self-sacrifice in [REC] acts as a deferring signifier of social deformity, one that might not achieve the goals of survival, infection or documentation but with each deferral makes the influence of hyper-competition in a modern, urban, cosmopolitan, European and Catalan context more evident.